The Influence of Motivation on Entrepreneurial Interest of FHB Students Duta Bangsa University Surakarta - Kurniawan, Tegar; Yusmaneti, Yusmaneti (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Interest in entrepreneurship is focusing attention on entrepreneurship because of a feeling of liking and accompanied by a desire to learn, know and prove more about entrepreneurship. Interest in entrepreneurship arises due to curiosity about information about entrepreneurship science which is then continued to participate directly in order to gain experience and finally the desire arises to pay attention to the experience that has been obtained. As well as having a feeling of joy and having the desire to be involved in risk-taking activities, to run your own business or venture by taking advantage of existing business opportunities, and creating new businesses with an innovative approach. One of the factors that influences the emergence of interest in entrepreneurship is entrepreneurial motivation. This research aims to determine the influence of entrepreneurial motivation on entrepreneurial interest among students at Duta Bangsa University, Surakarta. The quantitative research methodology with descriptive analysis used in this research is quantitative with descriptive analysis research type. The respondents in this research were 65 students from the Faculty of Business Law using the sampling method, namely saturated samples. The research results show that Achievement Motivation has a positive and significant influence on Entrepreneurial Interest with a score of 57.7%. These results can be interpreted as increasing Achievement Motivation in students will have an effect on increasing students' Entrepreneurial Interest.